Association of rs4680 COMT, rs6280 DRD3, and rs7322347 5HT2A With Clinical Features of Youth-Onset Schizophrenia - Morozova, Anna; Zorkina, Yana; Pavlov, Konstantin; Pavlova, Olga; Storozheva, Zinaida; Zubkov, Eugene; Zakharova, Natalia; Karpenko, Olga; Reznik, Alexander; Chekhonin, Vladimir; Kostyuk, Georgiy (Frontiers in Psychiatry, 2019)
We investigated the associations of rs4680 COMT, rs6280 DRD3 and rs7322347 5HT2A with youth-onset schizophrenia in the Russian population in a case-control study, and the role of the genotype in the severity of clinical features. The association between rs7322347 and schizophrenia (p = 0.0001) is described for the first time. Furthermore, we found a link with rs6280 and rs4680 in females (p = 0.001 and p = 0.02 respectively) and with rs7322347 in males (p = 0.002). Clinical symptoms were assessed on three scales: the Clinician-Rated Dimensions of Psychosis Symptom Severity scale, PANSS and FAB. Gender differences in clinical features are of particular interest. In our study we found gender differences in the severity of clinical features - higher scores for delusions (PANSS and DSM-V) in males and higher scores for depression, delusions, somatic concern, motor retardation, poor attention were found in females.